A STUDY OF THE SHORTEST-PERIOD PLANETS FOUND WITH KEPLER - Sanchis-Ojeda, Roberto; Rappaport, Saul; Winn, Joshua N.; Kotson, Michael C.; Levine, Alan; Mellah, Ileyk El (The Astrophysical journal, 2014)
We present the results of a survey aimed at discovering and studying transiting planets with orbital periods shorter than one day (ultra-short-period, or USP, planets), using data from the Kepler spacecraft. We computed Fourier transforms of the photometric time series for all 200,000 target stars, and detected transit signals based on the presence of regularly spaced sharp peaks in the Fourier spectrum. We present a list of 106 USP candidates, of which 18 have not previously been described in the literature. All 106 of our candidates have passed several standard tests to rule out false positives due to eclipsing stellar systems. By assuming these multi-transit candidates represent coplanar multi-planet systems, we are able to infer that the USP planets are typically accompanied by other planets with periods in the range 1-50 days, in contrast with hot Jupiters which very rarely have companions in that same period range.